2SPD-001 Use and cost evolution of infliximab and adalimumab over 8 years in a tertiary hospital. Issue 1 (23rd March 2023) - Gómez, A; Carrillo López, V; Lopez, M; Royo, V; Santandreu, MM; Pérez, MF; Khorrami, S; Iglesias, MC; Delgado, O; Ginard, D
Abstract : Background and Importance: The ongoing rise in healthcare costs makes it necessary to establish containment strategies, in parallel with the commitment to improve access to the most effective and safest treatments. The introduction of biosimilar medicines is an opportunity for health systems (HS) and patients. Aim and Objectives: The aim of the study was to evaluate the use and cost evolution of infliximab and adalimumab in the gastrointestinal department of a tertiary hospital over the last eight years. In this period, biosimilar molecules of both drugs have been incorporated. Material and Methods: Data were collected based on consumed units of adalimumab and infliximab between January 2014 and December 2021. We grouped the different presentations of original brand and biosimilar molecules available and the cost associated at the time it was consumed. Results: Both, infliximab and adalimumab, consumption have gradually increased over the past eight years, from 1, 774 to 2, 765 units (+55.9%) and from 920 to 3, 420 units per year (+271.7%), respectively. Infliximab biosimilar was introduced in the centre in 2015 and was progressively rolled out in starts and switches, becoming the sole since 2021. This has led to a gradual reduction in costs, from €852, 022 in 2014 to €497, 235 in 2021 (-41.6%). Adalimumab biosimilar was not introduced in the hospital until 2019. Consumption rose from 920 to 2, 153 units per year (+134.0%) between 2014 and 2018, in tandem with cost: from €442, 745 to €936, 175 per year (+111.5%). Nevertheless, between 2018 and 2021, consumption increases from 2, 153 to 3, 420 (+58.9%) with an absolute cost reduction of €563, 683 (-60.2%). Overall, adalimumab spending has decreased by 15.9% over the eight years despite the increase in consumption. Conclusion and Relevance: Innovation in biological therapies, as well as the increase in candidates to receive them, has grown significantly. It is associated with an increase in costs that may become unaffordable for public HS. The introduction of two biosimilar molecules in our centre has led to significant savings, despite the increase in consumption. The commercialisation of biosimilar molecules, alongside policies that allow their introduction in healthcare centres, promotes the system's sustainability, enables access to a greater number of patients, while allowing for the continued incorporation of innovative molecules. References and/or Acknowledgements: Conflict of Interest: No conflict of interest